Knowledge management in Malaysian nuclear agency: The first 40 years - Adnan, Habibah; Ngadiron, Norzehan; Ali, Iberahim (2012)
This paper gives an overview of nuclear knowledge management practices in Malaysian Nuclear Agency (Nuclear Malaysia) in the first 40 years of its operation. Nuclear Malaysia is established in 1972 and its main responsibility is to promote the application of nuclear technology in various socio-economic sectors including industry, medical, agriculture, manufacturing, health, radiation safety and the environment.Nuclear Malaysia’s core competency is R & D in nuclear science and technology.The explanation emphasizes on the activities and challenges in implementing NKM at the Nuclear Malaysia and in particular; nuclear knowledge management practices, the needs for Nuclear Malaysia to strengthen his KM activities and the evolvement and development of KM to enhance the ability of the organization.